THE EFFECTIVENESS OF QUIZZIZ ON TENTH GRADE EFL STUDENTS’ ACHIEVEMENT IN ENGLISH LEARNING PROCESS - Tio Nainggolan; Kadek Sintya Dewi (Universitas Pendidikan Ganesha, 2022)
This study aimed to find out the effectiveness of the use of Quizizz application in the English learning process for tenth-grade students. To select the representative sample, a purposive sampling method was used. The research design was a pre-test post-test which was used to collect data. This research uses one class as the research sample, namely class X MIPA 6 which consists of 35 students from SMA Negeri 1 Negara. During the research, they were taught using Quizizz in English class. To collect data, a method of giving a test was used. The data obtained showed the result of t-count is 5.757 with a significant 0.000 and the value of t on the t-table is 1.690. From the calculation above, t-count is bigger than the t-table (5.757> 1.690) and the result of Sig. (2-tailed) <0.05. Therefore, it can be stated that there is any significant difference between student English learning achievement before and after the implementation of Quizizz and Quizizz affects students’ English achievement.